2010
DOI: 10.5419/bjpg2010-0010
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Used Lubricant Oils Through Adsorption of Residues on Solid Surfaces

Abstract: Waste lubricant oils are products that undergo degradation due to their use, yielding substances that are potentially carcinogenic, such as PAHs (polycyclic aromatic hydrocarbons), which renders them improper. In this work, a sequence of physical steps was investigated focusing on the adsorption on solids for PAHs removal. Adsorption isotherms were constructed considering the PAHs concentration capacity presented by different solids, with activated carbon as the most efficient adsorbent in the removal of PAHs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The degradation of TBN value indicates regular oil changes [68,69]. Generally, the acidity in waste lube oils is removed by adsorbents, that is, activated clay, egg shale, almond shale, date palm kernel powder, acid activated date palm kernel powder, and walnut shale powders [18,31], alumina and silica gel [19], activated carbon, silica-gel, rice husk, silica-NH2, residues from acetylene synthesis, babaçu epicarp, and benzoin gum [70], chitosan powder, activated carbon and silica powder [17]. High-temperature membrane module is capable of treating used crankcase oils and providing a filtrate, which is free from suspended solids and dirt.…”
Section: Removal Of Acidity From Waste Lube Oilsmentioning
confidence: 99%
“…The degradation of TBN value indicates regular oil changes [68,69]. Generally, the acidity in waste lube oils is removed by adsorbents, that is, activated clay, egg shale, almond shale, date palm kernel powder, acid activated date palm kernel powder, and walnut shale powders [18,31], alumina and silica gel [19], activated carbon, silica-gel, rice husk, silica-NH2, residues from acetylene synthesis, babaçu epicarp, and benzoin gum [70], chitosan powder, activated carbon and silica powder [17]. High-temperature membrane module is capable of treating used crankcase oils and providing a filtrate, which is free from suspended solids and dirt.…”
Section: Removal Of Acidity From Waste Lube Oilsmentioning
confidence: 99%
“…These impurities contain dirt and metal parts that worn out from the engine parts. Waste metals from internal engines such as iron, lead, cadmium, chromium and other contaminants like water, dust and various impurities are absorbed and distributed into the various tissues of organism such as liver and kidney (Moura et al, 2010). At the end of toxicity test, we found that the kidneys from Control fish showed natural red colour whereas the kidney from exposed test fish were brownishblack in colour.…”
mentioning
confidence: 84%
“…The binary liquid mixtures of cyclohexane and t-butanol are also used as entertainers in azeotropic distillation process [14]. n-Butanol is the most efficient solvent for the extraction of the lubricating oils [15].…”
Section: Introductionmentioning
confidence: 99%